2008
DOI: 10.1097/mpa.0b013e31816074df
|View full text |Cite
|
Sign up to set email alerts
|

Serum Adhesion Molecules in Acute Pancreatitis

Abstract: This score seems to be useful for the early assessment of the severity of acute pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In a small study of Powell et al [132], serum soluble P-selectin concentrations during 3 days from admission did not differ between mild and severe AP, but were significantly higher in non-survivors than survivors. To the contrary, Pezzilli et al [123] reported lower soluble P-selectin in SAP patients’ sera as compared to those with mild AP and healthy controls.…”
Section: Laboratory Markers Of Endothelial Activation and Injury Imentioning
confidence: 98%
See 2 more Smart Citations
“…In a small study of Powell et al [132], serum soluble P-selectin concentrations during 3 days from admission did not differ between mild and severe AP, but were significantly higher in non-survivors than survivors. To the contrary, Pezzilli et al [123] reported lower soluble P-selectin in SAP patients’ sera as compared to those with mild AP and healthy controls.…”
Section: Laboratory Markers Of Endothelial Activation and Injury Imentioning
confidence: 98%
“…It was suggested that the peak soluble E-selectin concentrations are observed late (after 72 h from the onset of AP symptoms) and can therefore not be used as an early marker of AP severity [135,136]. During first 6 h from the onset of pain, Pezzilli et al [123] did not observe higher soluble E-selectin in AP patients compared to healthy controls; however, it was higher in SAP than in mild AP. Ida et al [126] did not show significant difference in soluble E-selectin on admission and on subsequent days in those who died from AP compared to survivors.…”
Section: Laboratory Markers Of Endothelial Activation and Injury Imentioning
confidence: 99%
See 1 more Smart Citation
“…Other markers of endothelial activation and dysfunction were shown to be increased in severe AP, including soluble E-selectin, tissue factor or von Willebrand factor and endothelial-specific microRNAs [5,11,12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…It is generally believed that inflammatory response plays a central role during this process [3,[8][9][10], of which the activation of ICAM-1, TLR4 and NF-κB proteins are important. Through mutual enhancements, these proteins can lead to deterioration in inflammatory injury [11][12][13][14][15][16]. Additionally, abnormal apoptosis present in multiple organs can also give rise to abnormal changes in the structure and function of these organs [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%